ANALISIS PERHITUNGAN BAGI HASIL YANG DITERIMA OLEH NASABAH PADA PT. BANK MUAMALAT CABANG AMBON - Albertus Lalaun (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2014)
This study aims to analyze the calculation profit-sharing received by the customers at PT. Bank Muamalat branch of Ambon. The method used in this research is quantitative descriptive analysis method. Processing method using a mathematical calculation based on the information available with compare theory and practice in the field. Location of the study is Bank Muamalat branch of Ambon, which is one of Shariah bank in the city of Ambon and operates with the principles of Shariah. Profit-sharing system used on its capital is Profit-sharing system of mudharaba and Profit-sharing system of Musharaka. Based on the analysis of Profit-sharing system can be found on average the results of the calculation as follows: for the results to client A reaches 7,921,290.24, for the results to client B reaches 7428387.429, for achieving results for clients C 7761295.037, for results for D customers achieve 7014193.769, and for the results to clients E reach 8992258.141.